Nickel-induced structure transformation in hydrocalumite for enhanced ammonia decomposition. (21st April 2020) - Zhao, Jiawen; Deng, Lidan; Zheng, Wei; Xu, Shuang; Yu, Qianqian; Qiu, Xinhong
Abstract: Modifying the material structure of catalysts and determining how the structure controls their catalytic activities are critical topics in heterogeneous catalysis research. Herein we report that the structure of hydrocalumite-layered double hydroxides (CaAl-LDHs) can be tuned by gradually introducting Ni 2+ . It was revealed that the gradual introduction of Ni 2+ in hydrocalumite led to a structure-transformation process, which introduced hydrombobomkulite and eventually evolved into takovite. Compared with the case without structure-transformation process, the structure-transformation catalysts showed excellent NH3 decomposition activity after high-temperature reduction. Moreover, the obtained catalysts showed a relatively high conversion per Ni weight compared with other reported oxide-supported Ni catalysts. This study demonstrates the feasibility of preparing LDHs-based heterogeneous catalysts by modulating the material structure through induced structure-transformation process. Graphical abstract: Image 1 Highlights: Modifying the structure of hydrocalumite by introducting Ni 2+ . The substitution of Ni 2+ in hydrocalumite led to a structure-transformation process. The structure-transformation catalysts showed excellent NH3 decomposition activity.